Tourism in Boracay Island the dilemma or resource utilization and management - Subade, Rodelio F.; Subade, Ana Liza A. (Danyag :the UPV journal of humanities and social sciences, 2006)
"Boracay Island has one of the world's most beautiful beaches. In recent years, tourist arrivals in the island have increased phenomenally and along with it, tourism's contribution to the local economy. Unfortunately, the natural environment of Boracay is a threatened ecosystem. In 1997, the Department of Environment and Natural Resources pronounced the island a disaster case with high levels of coliform in its waters. This study was undertaken eight years after the coliform outbreak to assess the status and usage of environment resources in Boracay. It employs key informant interviews, focus group discussions and review of secondary data to gather the necessary information. Results of the study showed that the environmental resources in Boracay Island have gone through unsustainable state of affairs. Uncontrolled development mainly due to tourism has resulted to more environmental problems. Despite the formulation of Boracay Island Management Development Plan, guidelines are hardly implemented. A tourism resource management that is broad-based, transparent, participatory, and responsive to environmental concerns and sustainability is needed to solve the environmental problems in Boracay."